ANALYSIS OF THE INFLUENCE OF THE WHITENING PROCESS DURING PREPARATION FOR FLOURING ON THE QUALITY OF BAKERY FLOUR MADE FROM A MIXTURE OF WHEAT AND RYE GRAINS - Kanoatov, Xayrullo; Qurayazov, Zaripbay; Ravshanov, Suvankul (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The article experimentally studies the effect of different methods of dry processing of the surface of local wheat and rye grains when preparing them for grinding into fine flour and their aging process during storage. The purpose of the study is to experimentally study the effect of different methods of dry processing of the surface of wheat and rye grains when preparing them for grinding into fine flour on the quality of bread products and their aging process. Materials and methods of research, sample bread was prepared from flours milled from a mixture of wheat and rye grains selected for the study in accordance with GOST 27669-88, their technological quality indicators were analyzed , and the results were processed using the full-factorial experimental method. The quality indicators of the bread sample prepared from the flour sample ground by dry processing on the proposed equipment showed the superiority of the specific volume of the bread, kernel porosity, ΔН index, bread volume and organoleptic assessment of bread quality over the samples ground on the current equipment used in production enterprises. It was proved that dry processing of the surface of this grain in preparing it for grinding into fine flour is of great technological importance in increasing the technological quality indicators of bakery products.